Impact of Crisis on Logistics Management - Daniel Constantin JIROVEANU; Ilinca HOTARAN (Revista de Management Comparat International)
Is the current situation facing the whole world and we need to adapt to withstand a fierce weather. Because the supply, which can be seen both as a sale (the manufacturers buy from suppliers) as well as a purchase (customers are supplied by producers) is the center of activities, we believe that a interpretation and a strategic direction to increase the competitiveness of extended supply chain, represents an initial starting point to save the current situation. We must understand that do not survive the nicest, smartest or the strongest, is the future of those who adapt best to change. In the global crisis context we must consider first the potential and not the market. Apparently the market is in a total collapse, but the potential still exists, even at minimum capacity it should work. Now they will be able to support only companies that eliminate almost all their losses and best manages their resources and activities.